Dirty Dance : Tourism and Environment - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2022)
Tourism was one of the fastest-growing sectors before the COVID-19 pandemic, accounting for about 10 percent of global GDP. But it has also created a number of challenges including environmental degradation, especially in small island countries where the carbon footprint of tourism constitute substantial share of carbon dioxide (CO2) emissions. This study empirically investigates the impact of tourism on CO2 emissions in a relatively homogenous panel of 15 Caribbean countries over the period 1960-2019. The results show that international tourist arrivals have a statistically and economically significant effect on CO2 emissions, after controlling for other economic, institutional and social factors. Therefore, managing tourism sustainably requires a comprehensive set of policies and reforms aimed at reducing its impact on environmental quality and curbing excessive dependency on fossil fuel-based energy consumption.